2011
DOI: 10.1523/jneurosci.0440-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Effort Drives Workspace Configuration of Human Brain Functional Networks

Abstract: Effortful cognitive performance is theoretically expected to depend on the formation of a global neuronal workspace. We tested specific predictions of workspace theory, using graph theoretical measures of network topology and physical distance of synchronization, in magnetoencephalographic data recorded from healthy adult volunteers (N ϭ 13) during performance of a working memory task at several levels of difficulty. We found that greater cognitive effort caused emergence of a more globally efficient, less clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
301
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(342 citation statements)
references
References 66 publications
37
301
1
3
Order By: Relevance
“…The coactivation network had more long-range connections. This is also compatible with an economical interpretation: integrative network features, such as long-range connections, incur a premium in terms of connection cost, emerging only under conditions where they can add value behaviorally in response to a cognitively challenging environment (10,40).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The coactivation network had more long-range connections. This is also compatible with an economical interpretation: integrative network features, such as long-range connections, incur a premium in terms of connection cost, emerging only under conditions where they can add value behaviorally in response to a cognitively challenging environment (10,40).…”
Section: Discussionsupporting
confidence: 66%
“…It has been shown that higher intelligence quotient is correlated with shorter topological path length of structural and functional networks, which would facilitate globally efficient, integrative processing (6,7). Other studies have shown network changes under contrasting experimental conditions (8)(9)(10). However, the reliance on resting-state functional MRI (fMRI) as the experimental basis for most work on functional networks has limited the extent to which the topology of brain graphs has been related to cognitive tasks, or to other aspects of brain function, such as local deactivations, which are well-established findings in task-related fMRI studies (11).…”
mentioning
confidence: 99%
“…In younger adults, this modular architecture facilitates the common processing roles of areas within similar systems while allowing communication between systems with distinct processing roles (21). Consistent with this, there is evidence for a relationship between measures of modularity and changes in task performance and learning in healthy young adults (49,50). Conversely, comparisons of younger and older adults have revealed differences in brainwide modularity in a direction consistent with the present observations (30,32,33,36).…”
Section: Rsfc-defined System Segregation As a Metric Of Functional Spsupporting
confidence: 87%
“…Examination of MEG data using these techniques has demonstrated that functional brain network organization is a biologically meaningful phenotype being altered in disease states (25) in ways that can be linked to behavioral task performance (60)(61)(62). Moreover, network organization demonstrates temporal variability that can be induced by cognitive remediation strategies (63), task practice (64), learning (41,53,65), or task difficulty (66).…”
Section: Discussionmentioning
confidence: 99%